The Role of Istiḥsān in the Dynamism of Muamalah Jurisprudence - Maghfiroh, Anisatul; Muslih, Imam; Cholili, Azwar; Muttaqin, Muh. Syaukin; Yasid, Abu (Islamic Micro Finance Journal, 2024)
Modern economic and social developments brought Muslim societies into the context of increasingly complex transactions, including banking, insurance, and others. This challenge raises new problems that are not only solved by the sources of Qur'anic law and hadith. Istiḥsān is a method of establishing law that is postulated in Hanafi fiqh, although its existence is still debated among fiqh scholars. This paper aims to examine the role of Istiḥsān as a method to find Islamic law, especially in the field of muamalah law. This research uses a desk-based research method, which includes searching relevant literature for data, compiling journal articles and books covering the subject matter of the research topic, and systematic analysis of the information obtained. The results of research in this paper show that istihsan is an important option in determining muamalah law, such as istitsna' transactions and bank interest, which can currently be settled by the istihsan method. In addition, istihsan also has the basic goal of eliminating mudharat and achieving maslahah